The Effect of Trichoderma sp on the Intensity of Fusarium Disease and Production of Shallot - Sataral, Mihwan; Nurdiansyah, Dzikri; Lamandasa, Frederik H (Jurnal Online Pertanian Tropik, 2020)
Fusarium wilt disease can cause damage and reduce the yield of shallot. Trichoderma sp is a biological agent that can be used to reduce the incidence of fusarium wilt disease in shallot. This study aims to determine the effect of Trichoderma sp on the intensity of fusarium wilt attack and shallot production. This research was conducted in Salodik Village, Luwuk Utara District, Banggai Regency, using a non-factorial randomized block design consisting of five treatments with four replications, namely: P0 (Control), P1 (10 gr Trichoderma sp./liter of water), P2 (12 gr Trichoderma sp./liter of water), P3 (14 gr Trichoderma sp./liter of water) and P4 (16 gr Trichoderma sp./liter of water). The results showed that giving Trichorderma sp had a very significant effect on the average intensity of fusarium wilt disease and had a significant effect on the average production of shallot. The provision of 10 gr Trichorderma sp /liter of water is the best treatment to reduce the intensity of fusarium wilt attack and increased the average production of shallot.